A new platypterygiine ichthyosaur rostrum from the Lower Cretaceous of the Lessini Mountains (Northern Italy) - Fornaciari, Beatrice; Maxwell, Erin; Papazzoni, Cesare Andrea; Zorzin, Roberto; FORNACIARI, ELIANA (Cretaceous Research, 2017)
An incomplete rostrum of a platypterygiine ichthyosaur (IGVR 94574) has recently been found near Tregnago (Verona, Italy), in the Lessini Mts. This is the first Cretaceous ichthyosaurian fossil found in Italy outside the northern Apennines, where fragmentary remains have been recovered since the 19th century. IGVR 94574 is a mid-distal rostral fragment infilled by a white, fine-grained limestone matrix. It consists of the premaxilla, nasal, vomer, dentary, and splenial, together with 20 teeth. Even if the exact horizon of provenance is unknown, analysis of the microfossil content of the matrix (planktonic foraminifera and calcareous nannofossils) allowed us to assign it to the lower part of the upper Albian. This is also the first Cretaceous ichthyosaur in Italy with a precise age: all previously reported fossils from the Apennines could not be dated due to the complete absence of microfossils in the surrounding matrix. We assign IGVR 94572 to Platypterygiinae; generic specification is not possible pending the taxonomic revision of the genus Platypterygius. Finally, the Tregnago rostrum is strikingly similar to the specimen IPUM 30139 from Gombola (Modena, Italy), stored in the collections of the Paleontological Museum of Modena and Reggio Emilia University and also attributable to a platypterygiine ichthyosaur. The comparison between these two fossils reveals the teeth are very similar both in shape and size.